The development of mechanisms of the evaluation of computer course and its impact on the development of motivation towards learning and achievement among students at the third preparatory grade in the light of Standard levels of teaching and e-learning - Seddik, Sameh Mohamed Mohamed (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed to determine the effect of the standardized levels e-learning through suitable for learning education and e-learning environments based on Web more so in terms of its impact on the development of skills, motivation and academic achievement among students at the third preparatory grade in unit programming computer decision, as well as to reach the most suitable electronic calendar methods through education and learning environments existing electronic web and commensurate with the learning style of the students in terms of achievement and motivation toward learning, and the development of e-electronic technical specifications codified file and the Court of a group of experts and specialists commensurate with the prep stage pupils, and use the same specification of the proposed model in the development of an assessment file (e-Portfolio) materials various scholarships for students in the preparatory stage. The study sample consisted of third graders preparatory in the (El- shheyed Ahmed Hamdi) and (prep old girls) governorate of Kafr El-Sheikh, Arab Republic of Egypt they are (80) students who have the basic skills to use computers and the Internet is available has been divided into experimental and control group two groups. The results of the study: - There were statistically significant differences at (05, 0) between the mean scores of the students in the experimental group two measurements pre and post the motivation toward learning scale, "in favor of telemetric" - There were statistically significant differences at (05, 0) between the mean scores of students of the experimental group and the control group in the dimensional measurement on the scale of motivation toward learning, "for the experimental group." - There were statistically significant differences at the level of significance (0.05) among the middle ranks of the experimental group students in pre and post application of the test grades in favor of telemetric - There were statistically significant differences at the level of significance (0.50) between the average scores of the experimental group students and the average score of the control group in the post application of the test grades for the experimental group.
Keywords: evaluation mechanisms; e-learning; motivation; achievement